Gender Differences in the Effects of Vocational Training : Constraints on Women and Drop-out Behavior - Cho, Yoonyoung (World Bank, Washington, DC, 2013)
This paper provides experimental evidence on the effects of vocational and entrepreneurial training for Malawian youth, in an environment where access to schooling and formal sector employment is extremely low. It tracks a large fraction of program drop-outs -- a common phenomenon in the training evaluation literature -- and examines the determinants and consequences of dropping out and how it mediates the effects of such programs. The analysis finds that women make decisions in a more constrained environment, and their participation is affected by family obligations. Participation is more expensive for them, resulting in worse training experience. The training results in skills development, continued investment in human capital, and improved well-being, with more positive effects for men, but no improvements in labor market outcomes in the short run.